Investigation of mechanical properties of silver-doped diamond-like carbon coating by varying deposition temperature - Ghadai, Ranjan Kr.; Shanmugasundar, G.; Vanitha, M.; Čep, Robert; Das, Soham; Swain, Bibhu P. (Frontiers in Mechanical Engineering, 2024)
The present work shows the influence of deposition temperatures over the mechanical properties of silver (Ag) doped diamond like carbon (DLC) coating synthesized by thermal chemical vapour deposition (CVD) technique. The deposited film shows excellent mechanical and tribological behavior with respect to the lower deposition temperatures. From the EDS analysis it is confirmed that the percentage of Ag decreases from 9.8 to 8.4 % with increasing the deposition temperature. The nanoindentation tests at different loads were extensively carried out to observe the mechanical properties of the coating with respect to various deposition temperatures.The coating hardness (H) and young's modulus (E) decreases with rise in furnace temperature and the Hmax. and Emax. were observed as 29.71 and 251.19 GPa for the Ag-DLC coating grown at 800 o C at a load of 20 mN. In comparison to other Ag-DLC thin films made using different deposition techniques, the residual stress (𝝈) has been significantly reduced, reaching 0.45 GPa, which is extremely low.